Characterization of human transcription factor function and patterns of gene regulation in HepG2 cells - Moyers, Belle A.; Partridge, E. Christopher; Mackiewicz, Mark; Betti, Michael J.; Darji, Roshan; Meadows, Sarah K.; Newberry, Kimberly M.; Brandsmeier, Laurel A.; Wold, Barbara J.; Mendenhall, Eric M.; Myers, Richard M. (Genome Research, 2023)
Transcription factors (TFs) are trans-acting proteins that bind cis-regulatory elements (CREs) in DNA to control gene expression. Here, we analyzed the genomic localization profiles of 529 sequence-specific TFs and 151 cofactors and chromatin regulators in the human cancer cell line HepG2, for a total of 680 broadly termed DNA-associated proteins (DAPs). We used this deep collection to model each TF's impact on gene expression, and identified a cohort of 26 candidate transcriptional repressors. We examine high occupancy target (HOT) sites in the context of three-dimensional genome organization and show biased motif placement in distal-promoter connections involving HOT sites. We also found a substantial number of closed chromatin regions with multiple DAPs bound, and explored their properties, finding that a MAFF/MAFK TF pair correlates with transcriptional repression. Altogether, these analyses provide novel insights into the regulatory logic of the human cell line HepG2 genome and show the usefulness of large genomic analyses for elucidation of individual TF functions.
10.1101/gr.278205.123